THE ROLE OF SUSTAINABILITY ACCOUNTING AND ITS REFLECTION IN DIGITAL FINANCIAL SERVICES FOR BANKS A FIELD STUDY ON IRAQI COMMERCIAL BANKS- DIWANIYAH (World Economics and Finance Bulletin, 2024)
The study aims to analyze the role of Sustainability Accounting and its reflection in digital financial services in Iraqi commercial banksDiwaniyah , The study was based on a descriptive-analytical approach to measure its variables The five-factor Likert scale was used as a tool to collect data from a sample consisting of (106) factors , The study focused on an important question that the role of Sustainability Accounting and its reflection in digital financial services at Iraqi commercial banks-Diwaniyah , In order to address these problems, the study adopted two packages to analyze the results based on (SPSS.V.28 & SMART.PLS), As a result, the study came out with a set of results, the foremost of which was the existence of a role for Sustainability Accounting in the digital financial services of banks, and this contributed to clarifying how sustainability practices affect the development and provision of digital financial services, Sustainability Accounting contributes to enhancing the social responsibility of banks and reducing the environmental impact of their financial activities , The study concluded with a set of recommendations, the most important of which is the need to develop training and awareness programs for bank employees , With the aim of developing the necessary skills to assess and analyze the social and environmental impact of digital financial services and increasing awareness of Sustainability Accounting and its impact on digital financial services
Keywords: Sustainability Accounting; digital financial services; Iraqi commercial banks